1974
DOI: 10.1002/qj.49710042507
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the nocturnal atmospheric boundary layer

Abstract: The evolution of the structure of the atmospheric boundary layer during the cooling phase of the diurnal cycle is studied with the help of a one-dimensional numerical model. The model uses a turbulent energy equation for the determination of the eddy exchange coefficients, which also involve the local value of the Monin-Obukhov length. The surface temperature is prescribed as a function of time and the geostrophic wind is held constant. Results are presented in nondimensional form and cover a wide range of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The investigation of the length-scale of the wind profile was initiated by Prandtl (1925), who introduced the concept of the mixing length when analyzing mean velocity profiles in laboratory flows. Prandtl's work has motivated the use of mixing-length theory for the entire boundary layer (Blackadar, 1962;Lettau, 1962;Delage, 1974;Gryning et al, 2007). This has been used to derive wind profile parameterizations that fit wind speed observations performed beyond the surface layer both over land and water surfaces (Gryning et al, 2007;Peña et al, 2008Peña et al, , 2010a better than traditional surface-layer theory.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the length-scale of the wind profile was initiated by Prandtl (1925), who introduced the concept of the mixing length when analyzing mean velocity profiles in laboratory flows. Prandtl's work has motivated the use of mixing-length theory for the entire boundary layer (Blackadar, 1962;Lettau, 1962;Delage, 1974;Gryning et al, 2007). This has been used to derive wind profile parameterizations that fit wind speed observations performed beyond the surface layer both over land and water surfaces (Gryning et al, 2007;Peña et al, 2008Peña et al, , 2010a better than traditional surface-layer theory.…”
Section: Introductionmentioning
confidence: 99%
“…Thorpe and Guymer (1977), Beyrich and Klose (1988), and Singh et al (1993) further modified the one-dimensional Blackadar theory of the nocturnal low-level jet by considering a variety of stress parametrizations, though with various structural or dynamical features treated as vertically discontinuous, slab-like or layered. Wippermann (1973), Delage (1974), Brook (1985), and Davies (2000) extended the Blackadar conceptual model by incorporating vertically continuous (apart from numerical discretization) turbulent stress parametrizations in their one-dimensional planetary boundary layer models. Recent advances in computer technology are making large-eddy simulation (LES) of the Blackadar jet scenario increasingly feasible, with some simulations extending over the daytime dry convective regime, the evening transition period, and the nocturnal period during which the jet develops.…”
Section: Introductionmentioning
confidence: 99%
“…This fact can be taken into consideration by adopting the inverse linear approximation of Delage (1974), between the limits of the mixing length near the underlying surface (= κz) and in the neutral boundary layer (= λ o ) : 1/l = 1/(κz)+1/(λ o ), which is equivalent to l = z/(1 + κz/λ o ). Blackadar (1962) suggested that λ o = 0.009u * / f , where f is the Coriolis parameter.…”
Section: Governing Equationsmentioning
confidence: 99%